العربية والإعراب: بين ادّعاء الاصطناع، وشرعية الأصالة - نبيلة, قريني (جامعة الوادي - University of Eloued, 2021)
الملخص: تعدّ اللغة العربية من اللغات المعربة؛ إذ تعتمد في تغيير المعاني على تغيّر أواخر الكلمات في التركيب. وبالرغم من ثبوت هذه الخاصية اللغوية في النصوص الفصيحة، فقد تعالت ادّعاءات من مستشرقين وعرب على حد سواء مفادها أن الإعراب ليس خاصية أصيلة في العربية، وإنما هو آلية اصطنعها النحويون وألحقوها باللغة، ثم ألزموا أهلها اتّباعها. وفي مقابل هؤلاء انبرى جمع من اللغويين المحدثين يردّون زيف ذلك الادّعاء، واجتهدوا في إثبات أصالة الإعراب في العربية. وسنحاول في هذا المقال تسليط الضوء على هذه المسألة من باب التذكير بخطورتها وأبعادها الفكرية والحضارية. Abstract: Arabic language is one of the parsing languages. It relies, in changing the meanings, on the change of the last letters composing the words. Although this linguistic feature has been proven in the classical texts, both orientalists and Arabs have claimed that parsing is not an original feature of Arabic language, but rather a mechanism which was artificialized by grammarians who joined it to the language then obligated people to follow it. In contrast, a group of modern linguists rejected this false claim and deployed efforts to prove the authenticity of the Arabic expression. In this article, we will try to shed the light on this issue as a reminder of its seriousness and its intellectual and cultural dimensions.
مقال
Keywords: لإعراب، الاصطناع، الأصالة، المستشرقون، اللغويون العرب; linguists. Arabic language, parsing, artificiality, originality, orientalists, Arab